The Motive of Lycanthropy in A.I. Kuprin’s Short Story “The Silver Wolf” - Puponin, Dmitry Valerevich (The Lingua Spectrum, 2026)
The article explores the motive of lycanthropy (werewolfism), one of the most representative mystical motives in the prose of A.I. Kuprin. The short story “The Silver Wolf” (1901) is chosen as the object of the study. The introductory part provides an overview of contemporary literary studies (predominantly by Russian scholars) addressing the interpretation of the concept of “motive”. The main body of the work examines the artistic aspects of “The Silver Wolf,” with particular focus on the structure and characteristics of the lycanthropy motive (the protagonist, Stetsko, is a volkulak – a werewolf). The narrative motive of the human-to-wolf transformation in this work is primarily linked to the rite of initiation. All key elements of this ancient rite find their artistic realization in “The Silver Wolf”: temporary death (the hero’s experience at war); the presence of physical injuries and traumas (bullet wounds, lameness); and the acquisition of magical abilities (transformation into a wolf). It is also significant that the hero takes the form of a wolf in his animal incarnation. In Slavic folk culture, the wolf is often identified as a “stranger” or an “outsider.” Stetsko, returning from the war, likewise becomes a “stranger” to his fellow villagers. The concluding part of the work provides a generalized characterization of the structure of the lycanthropy motive in A.I. Kuprin’s story.